Mathematical Communication Ability of Madrasah Aliyah Students Given Self-Confidence and Learning Independence - Handayani, Rizki; Siregar, Nurhasanah; Simanjuntak, Erlinawaty; Molliq, Yulita (PYTHAGORAS Jurnal Matematika dan Pendidikan Matematika, 2024)
The research aims to ascertain how mathematical communication ability is impacted by self-confidence, how learning independence affects mathematical communication ability, and how self-confidence and learning independence affect mathematical communication ability in 11th-grade students at MA Muhammadiyah 1 Medan in the 2023–2024 academic year. This is a correlational study with a quantitative methodology. This research used cluster sampling, and the total sample size was 31 students. This study collected data using questionnaires and tests. The research instruments used were self-confidence and learning independence questionnaires, as well as mathematical communication ability tests. Multiple regression analysis was used in this study's data analysis procedures. The analysis's findings indicate that self-confidence impacts on mathematics communication with a value of sig. 0.025 and a value of tcount 2.317; learning independence impacts on mathematics communication ability, with a value of sig. 0.12 and the value of tcount 2.512; self-confidence and learning independence positively and significantly impact on mathematics communication ability, with a value of . 0.000; and a coefficient of determination of 0.612, implying that self-confidence and learning independence affect mathematical communication by 61.2%.